Glaziale und periglaziale Lebensräume im Raum Obergurgl - Koch, Eva-Maria (Alpine Forschungsstelle Obergurgl, 2010)
Glaciers and glacier forelands are the most impressive landscapes in the inner Oetz Valley (Tyrol, Austria). Since 1858, the glaciers of the area are retreating more or less continuously, releasing new areas for colonization. The main aim of book no. 1 of the Alpine Research Centre Obergurgl is to present the research at the Rotmoosferner glacier foreland and the knowledge of glacial environments in a comprehensive way. The book provides baseline informations for students, prospective scientists, field courses and for interested lay people.